A implantação de parques lineares urbanos na perspectiva ambiental e social: um estudo de caso do córrego Bezerra Cascavel – PR - Paciornik, Deborah de Camargo (2018)
It is known that permanent preservation areas play an essential role for the conservation of water resources, fauna and flora of urban and rural ecosystems, but the constant urban expansion and human neglect of them tend to have a negative impact on these natural areas. The objective of this study is to analyze the revitalization model of permanent preservation areas (APP) by creating linear parks, in order to contribute to the environmental management of urban water resources, using Córrego Bezerra as a case study. This work has a qualitative research approach where the bibliographic review, the documentary analysis and the case study were used. This study was carried out in two stages: the diagnosis of the study area, through a photographic survey, data collection by thematic maps and documents provided by public agencies; and social analysis, through semi-structured interviews, using the saturation method. Therefore, the present study shows how these factors influence the revitalization of the Córrego Bezerra and its riparian forest, as well as how the implantation of an urban linear park would influence the environmental and social dynamics of the western region of the city of Cascavel.